Requirements for the Sustainable Development of Economic Activities in Tropical Forest Communities - Mechik, Elena; von Hauff, Michael (European Journal of Sustainable Development, 2016)
Tropical forests are storing carbon in their biomass, supporting biodiversity, acting as sources for timber and Non Timber Forest Products, and are the habitat for forest communities. For centuries, most tropical forest communities maintained sustainable forest management, which has led to the sustainment of their living conditions and to an important contribution to the conservation of the environment and the climate. In the last decades this is increasingly threatened by the commercial timber industry which plunders the tropical forests for the extraction of valuable timber. In this paper we propose a concept of how sustainable development concept can be applied to the living conditions of tropical forest communities. We answer the question of how sustainable development of economic activities for forest communities’ inhabitants can be achieved including improvement of their living standard and conservation of tropical forests. We formalize qualitative causal relations and conclude that sustainable development in forest communities cannot be achieved without 1. legal rights for forest management, 2. targeted investments and initial capital for the organization of economic activities with ecological and social responsibility, and 3. organizational, technical, and methodical support. Keywords: sustainable development; tropical forest communities; small scale forest enterprises; social responsibility